Accounting for the instrument function of crystal spectrometers operating in many reflection orders in the diagnostics of laser plasma from its continuum spectrum. (September 2018) - Alkhimova, M.A.; Skobelev, I.Yu.; Faenov, A.Ya.; Arich, D.A.; Pikuz, T.A.; Pikuz, S.A.
Abstract: By the example of an X-ray spectrometer with a spherically bent mica crystal we consider the diagnostic errors entailed when the observed bremsstrahlung spectrum is attributed to a single spectrum of reflection. As an illustration we choose the X-ray emission spectrum of the plasma produced at the surface of a steel foil by femtosecond laser pulses of relativistic intensity. It is shown that obtaining adequate results in the case of a high-temperature plasma calls for the consistent inclusion of all orders of reflection or diffraction with a dispersing device.